Assessment of multiple stressors on the growth of larval green sturgeon Acipenser medirostris: implications for recruitment of early life‐history stages. Issue 5 (29th November 2018) - Poletto, Jamilynn B.; Martin, Benjamin; Danner, Eric; Baird, Sarah E.; Cocherell, Dennis E.; Hamda, Natnael; Cech, Jr, Joseph J; Fangue, Nann A.
Abstract : Early developmental stages of fishes are particularly sensitive to changes in environmental variables that affect physiological processes such as metabolism and growth. Both temperature and food availability have significant effects on the growth and survival of larval and juvenile fishes. As climate change and anthropogenic disturbances influence sensitive rearing environments of fishes it is unlikely that they will experience changes in temperature or food availability in isolation. Therefore, it is critical that we determine the effects of each of these potential stressors on larval growth and development, as well as understand the additive, synergistic or antagonistic effects of both. We reared threatened green sturgeon Acipenser medirostris (initial age ca. 32 days post hatch) at four temperatures (11, 13, 16 and 19°C) and two food availability rates (100% and 40% of optimal) to assess the effects of these stressors and their interactions on larval growth. We compared the overall size (fork length, total length and mass), growth rates (cm day −1 and g day −1 ) and relative condition factor of these larval and juvenile fish at 3 week intervals for up to 12 weeks. Our results indicated that temperature and food availability both had significant effects on growth and condition and that there was a significant interaction between the two. Fish reared with limited food availability exhibited similar patterns in growth rates to those reared with elevated food rates, but the effects of temperature were greatly attenuated when fish were food‐limited. Also, the effects of temperature on condition were reversed when fish were reared with restricted food, such that fish reared at 19°C exhibited the highest relative condition when fed optimally, but the lowest relative condition when food was limited. These data are critical for the development of relevant bioenergetics models, which are needed to link the survival of larval sturgeons with historic environmental regimes, pinpoint temperature ranges for optimal survival and help target future restoration sites that will be important for the recovery of sturgeon populations.